Trichloroisocyanuric acid, a New and Efficient Catalyst for the Synthesis of 2′- Aminobenzothiazolo-arylmethyl-2-naphthols. Issue 4 (2012) - Yang, Limin
Abstract : An efficient one-pot synthesis of 2′-aminobenzothiazolo-arylmethyl-2-naphthols is described. This involves the three-component reaction of β -naphthol, aromatic aldehydes and 2-aminobenzothiazole in the presence of a catalytic amount of trichloroisocyanuric acid under solvent-free conditions.